Genetic Control of Rod Bipolar Cell Number in the Mouse Retina - Kautzman, Amanda G.; Keeley, Patrick W.; Borhanian, Sarra; Ackley, Caroline R.; Reese, Benjamin E. (Frontiers in Neuroscience, 2018)
Genetic variants modulate the numbers of various retinal cell types in mice. For instance, there is minimal variation in the number of rod bipolar cells (RBCs) in two inbred strains of mice (A/J and C57BL/6J), yet their F1 offspring contain significantly more RBCs than either parental strain. To investigate the genetic source of this variation, we mapped the variation in the number of RBCs across 24 genetically distinct recombinant inbred (RI) strains (the AXB/BXA strain-set), seeking to identify quantitative trait loci (QTL). We then sought to identify candidate genes and potential casual variants at those genomic loci. Variation in RBC number mapped to three genomic loci, each modulating cell number in excess of one-third of the range observed across the RI strains. At each of these loci, we identified candidate genes containing variants that might alter gene function or expression. The latter genes were also analyzed using a transcriptome database, revealing a subset for which expression correlated with variation in RBC number. Using an electroporation strategy, we demonstrate that early postnatal expression of one of them, Ggct (gamma-glutamyl cyclotransferase), modulates bipolar cell number. We identify candidate regulatory variants for this gene, finding a large structural variant in the putative promoter that reduces expression using a luciferase assay. This structural variant reducing Ggct expression in vitro is likely the causal variant within the gene associated with the variation in Ggct expression in vivo, implicating it as a quantitative trait variant (QTV) participating in the control of RBC number.